The economic and financial situation of the dependency system: an induced unsustainability - Durán Bernardino, Manuela (Revista de Trabajo y Seguridad Social. CEF, 2014)
The System for Autonomy and Care for dependence is facing serious financial problems that threaten their protective action. This reality makes this timely article, where funding of the System for Autonomy and Care for Dependency before the transcendent legislative and budgetary changes in recent years is analyzed. Specifically, the study of the three direct founders System Dependency is addressed: the General Administration of State through the State Budget funds a Minimum Level of protection increasingly smaller and Agreed Level that is currently suspended; autonomous communities, which support the direct cost of services and benefits; and users, who see their contribution to increased system cost (co-payment). The result is a situation of unsustainable financial stress need for an urgent review and reform.